A Robust Symbiotic Relationship Between the Ciliate Paramecium multimicronucleatum and the Bacterium Ca. Trichorickettsia Mobilis - Mironov, Timofey; Sabaneyeva, Elena (Frontiers in Microbiology, 2020)
Close reciprocal interactions in symbiotic systems have suggested the holobiont concept, in which the host and its microbiota are considered as a single entity. Ciliates are known for their ability to form symbiotic associations with prokaryotes. Relationships between the partners in such systems vary from mutualism to parasitism and differ significantly in their robustness. We assessed the viability of the ciliate Paramecium multimicronucleatum and its ability to maintain its intranuclear endosymbiont Ca. Trichorickettsia mobilis (Rickettsiaceae) after treatment with antibiotics characterized by different mode of action, such as ampicillin, streptomycin, chloramphenicol, tetracycline. The presence of endosymbionts in the host cell was determined by means of living cell observations made using differential interference contrast or fluorescence in situ hybridization with the species-specific oligonucleotide probe (FISH). Administration of antibiotics traditionally used in treatments of rickettsioses, tetracycline and chloramphenicol, depending on the concentration used and the ciliate strain treated, either caused death of both, infected and control cells, or did not affect the ability of the host to maintain the intranuclear endosymbiont. The surviving cells always manifested motile bacteria in the macronucleus. Streptomycin treatment never led to the loss of endosymbionts in any of the four infected strains, and nearly all ciliates remained viable. Ampicillin treatment never caused host cell death, but resulted in formation of filamentous and immobile oval bacterial forms. Under repeated ampicillin treatments, a part of endosymbionts was registered in the host cytoplasm, as evidenced both by FISH and transmission electron microscopy. Endosymbionts located in the host cytoplasm were enclosed in vacuoles, apparently, corresponding to autophagosomes. Nevertheless, the bacteria seemed to persist in this compartment and might cause relapse of the infection. Although the antibiotic sensitivity profile of Trichorickettsia seems to resemble that of other representatives of Rickettsiaceae, causative agents of severe diseases in humans, neither of the antibiotic treatments used in this study resulted in an aposymbiotic cell line, apparently, due to the protists' sensitivity to tetracyclines, the drugs of preference in rickettsiosis treatment. The observed robustness of this symbiotic system makes it a good model for further elaboration of the holobiont concept.